A qualitative assessment of the perceptions and attitudes towards commercial tobacco policies and education among tribal communities in California. (2nd January 2022) - Soto, Claradina; Ramos, Guadalupe; Martinez, Desirae; Moerner, Lou; Salinas, Erika; Battle, Robynn; Yerger, Valerie
ABSTRACT: Background : California has the largest American Indian and Alaska Native (AIAN) population in the United States and faces several commercial tobacco related disparities. This study assessed current interest, readiness, and knowledge regarding commercial tobacco control policies in California Tribal communities. Objectives : A community readiness assessment was conducted in California Tribal communities to understand commercial tobacco policies that included: Tobacco 21 (California State, and now federal, law restricting commercial tobacco sales to age 21 and over), tobacco tax, smoke-free worksites on Tribal lands, smoke-free households, and smoke-free indoor and outdoor areas in multi-unit housing. Methods : Twelve Tribal communities participated in focus groups and interviews between 2016–2019. Content analysis was utilized to code and data were analyzed using ATLAS.ti software. Results : A total of 165 community members participated (65% female), with most expressing support for unwritten, community-based "small p" policies, (e.g., placing signage to create a smoke-free perimeter). However, there was little to no support for "big P" policies (e.g., written ordinances on smoke-free casinos, smoke-free housing). Support for tobacco product taxation varied. The importance of Tribal sovereignty and the need for tobacco prevention and cessation programs for youth were two additional topics that emerged. Conclusions : Participants supported Tribal policies and wished for outsiders to respect Tribal sovereignty in this regard. Communities are currently working to raise awareness about the dangers associated with commercial tobacco use and would benefit from the responsiveness of future funders to these requests.